Recent advances in bioactive hydrogel microspheres: Material engineering strategies and biomedical prospects - Junjiang Yue; Zhengbiao Liu; Lu Wang; Miao Wang; Guoqing Pan (Materials Today Bio)
Hydrogel microspheres are a class of hydrophilic polymeric particles in microscale, which has been developed as a new type of functional biomaterials for wide-range biomedical applications in recent years. This review provides a comprehensive overview of the preparation methods for hydrogel microspheres, including droplet microfluidics, electrospray and emulsion was first summarized. At the same time, we analyze the impacts of these methods on the properties of hydrogel microspheres and explore various functionalization strategies for enhancing their bioactivity and expanding their biomedical applications. In addition, we discuss the recent advances and the further prospect of hydrogel microspheres in life science applications, particularly in cell biology research, bioanalysis and detection, as well as tissue repair and regeneration. By synthesizing the latest developments, this review aims to offer valuable insights and strategies for optimizing hydrogel microspheres in diverse application scenarios and inspire future research and practical innovations.